Jak uczyć o Holokauście w szkole ponadgimnazjalnej? - Kotelnicka, Beata (Dydaktyka Polonistyczna, 2017)
This text concerns the issue of the Holocaust discussed in didactic perspectives: goals, methodsof work in a high school and set books. General issues are explained in a didactic project based onfilmed witness account (Rachel Nussbaum)and referred to cultural texts discussed in a high school.Teacher will find here resources required for a lesson related to the Holocaust (texts, list of tasks,worksheets, scheme of ghetto in Rzeszow) with some tips how to use them. The aim of the Holocaustclass is to structure ethically appropriate comportment of a young generation